Autoimmune polyglandular syndrome type 4: experience from a single reference center - Gatta, Elisa; Anelli, Valentina; Cimino, Elena; Di Lodovico, Elena; Piovani, Elda; Zammarchi, Irene; Gozzoli, Giorgia; Maltese, Virginia; Cavadini, Maria; Agosti, Barbara; Delbarba, Andrea; Pirola, Ilenia; et al. (Frontiers in Endocrinology, 2023)
Purpose. To characterize patients with APS type 4 among those affected by APS diagnosed and monitored at our local Reference Center for Autoimmune Polyglandular Syndromes. Methods. Monocentric observational retrospective study enrolling patients affected by APS diagnosed and monitored in a Reference Center. Clinical records were retrieved and analyzed. Results. 111 subjects (51 males) were affected by APS type 4, mean age at the onset was 23.1 ± 15.1 years. In 15 patients the diagnosis of APS was performed during the first clinical evaluation, in the other 96 after a latency of 11 years (range 1-46). The most frequent diseases were type I diabetes mellitus and celiac disease, equally distributed among sexes. Conclusions. The prevalence of APS type 4 is 9:100,000 people. Type I diabetes mellitus was the leading indicator of APS type 4 in 78% subjects and in 9% permitted the diagnosis occurring as second manifestation of the syndrome. Our data, showing that 50% of patients developed APS type 4 within the first ten years, don’t suggest any particular follow-up time and, more importantly, don’t specify any particular disease. It is important to emphasize that 5% of women developed premature ovarian failure.